Lithium tantalate wafer grinding wheel and preparation method thereof
By adding elements such as Al and Mg to the SiC powder/Cu composite material, the intermetallic compounds are prepared and formed at low temperature, which solves the problem of poor interfacial reaction and wetting performance of existing materials during processing, and achieves a composite material with high thermal conductivity and high strength, meeting the processing needs of lithium tantalate wafers.
Patent Information
- Application Number
- CN202411573891.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-28
AI Technical Summary
During the processing process, existing SiC powder/Cu composites have problems such as interfacial reaction, silicon element diffusion, and poor wetting performance, resulting in low thermal conductivity and strength, which cannot meet more stringent requirements.
By adding elements such as Al and Mg, SiC powder/Cu composites are prepared at low temperature to form intermetallic compounds to avoid harmful interface reactions, and systematically study the impact of SiC powder volume fraction on the composite materials, and develop the best thermal conductivity formula.
It realizes SiC powder/Cu composite materials with high thermal conductivity and high strength to meet the processing needs of lithium tantalate wafers, effectively avoiding the problems of burns on the surface of the workpiece and low processing accuracy.
Smart Images

Figure CN119526285A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of grinding wheels, and more particularly to a lithium tantalate wafer grinding wheel with high thermal conductivity and a preparation method thereof. Background Art
[0002] Lithium tantalate (LiTaO3, LT) single crystal is an excellent piezoelectric crystal material with advantages such as large piezoelectric coefficient, small frequency temperature coefficient and high electromechanical coupling coefficient. It is widely used in laser technology to make Q-switches, infrared technology as pyroelectric detectors, and electronics industry to make filters and resonators. The most widely used application of lithium tantalate is to make surface acoustic wave filters. Its outstanding advantages are low delay time temperature coefficient, only 18ppm in the range of -20 to 80℃, and good thermal stability of the device. However, lithium tantalate itself has a strong pyroelectric effect. Changes in temperature during the device preparation process will cause discharge on the surface of the material. This pyroelectric effect may damage the substrate pattern or even destroy the substrate material.
[0003] SiC powder has low density, high strength, high hardness, good thermal conductivity, electrical conductivity and thermal stability, while Cu has excellent thermal and electrical conductivity. Composite materials with high thermal conductivity and high strength made of SiC powder and Cu are widely used in electronic packaging, electrical appliances, heat exchange equipment, aerospace fields (such as aircraft frames), automotive fields (such as brake pads, internal combustion engine pistons and engine impellers), and electrode materials in the welding industry.
[0004] Although SiC powder / Cu composite materials have made great progress, there are still problems such as interface reaction between SiC powder particles and copper in direct contact, diffusion of silicon elements into the copper matrix after decomposition of SiC powder, and poor wetting performance between SiC powder and copper. As a result, the thermal conductivity and strength of SiC powder / Cu composite materials are not high and cannot meet more stringent requirements. Summary of the invention
[0005] In view of the shortcomings of the prior art described above, the purpose of the present invention is to provide a lithium tantalate wafer grinding wheel and a preparation method thereof, add Al, Mg, etc., prepare SiC powder / Cu composite materials at low temperature, form intermetallic compounds while effectively avoiding harmful interface reactions, prepare composite materials with high thermal conductivity and high strength, and systematically study the effect of SiC powder volume fraction on the density, microstructure, mechanical properties and thermal properties of the composite materials. The optimal thermal conductivity formula of the developed SiC powder / Cu composite material meets the processing requirements of lithium tantalate wafers.
[0006] The present invention first provides a lithium tantalate wafer grinding wheel, which comprises a substrate and a circular ring block arranged circumferentially on the top end surface of the substrate, wherein the circular ring block constitutes an abrasive layer of the grinding wheel, and the abrasive layer comprises the following powder raw materials in proportions by volume: 18 to 25 parts of artificial single crystal diamond powder; 30 to 35 parts of SiC powder; 45 to 52 parts of copper powder; 7 to 9 parts of aluminum powder; and 2 to 4 parts of magnesium-aluminum alloy powder.
[0007] In one embodiment, the mass ratio of magnesium to aluminum in the magnesium-aluminum alloy powder is 9:1.
[0008] In one embodiment, based on the total volume of SiC powder, copper powder, aluminum powder and magnesium-aluminum alloy powder being 100%, the volume fraction of the SiC powder is greater than 30% and less than 40%.
[0009] In one embodiment, the SiC powder is green SiC powder, the copper powder is electrolytic copper powder, the aluminum powder is electrolytic aluminum powder, and the magnesium-aluminum alloy powder is electrolytic magnesium-aluminum alloy powder.
[0010] In one embodiment, the average particle size of the SiC powder is 26-27 μm, the average particle size of the copper powder is 7-8 μm, the average particle size of the aluminum powder is 17-18 μm, and the average particle size of the magnesium-aluminum alloy powder is 32-33 μm.
[0011] In one embodiment, the particle size of the artificial single crystal diamond powder is 20-24 μm.
[0012] Another aspect of the present invention further provides a method for preparing a lithium tantalate wafer grinding wheel, the preparation method comprising the following steps:
[0013] - S1: SiC powder, copper powder, aluminum powder and magnesium aluminum alloy powder are mixed to obtain a mixture A;
[0014] - S2: crushing and sieving the artificial single crystal diamond to obtain artificial single crystal diamond powder;
[0015] - S3: Mixture A and the artificial single crystal diamond powder are mixed to obtain mixture B;
[0016] - S4: forming and curing the mixed material B to obtain the lithium tantalate wafer grinding wheel;
[0017] Among them, the lithium tantalate wafer grinding wheel includes a base and a circular ring block arranged circumferentially on the top end surface of the base, the circular ring block constitutes the abrasive layer of the grinding wheel, and the abrasive layer includes the following volume proportions of powder raw materials: 18 to 25 parts of artificial single crystal diamond powder; 30-35 parts of SiC powder; 45-52 parts of copper powder; 7 to 9 parts of aluminum powder; 2 to 4 parts of magnesium-aluminum alloy powder.
[0018] In step S1, the mixing may include stirring, the medium for stirring may be ethanol, and the stirring is performed by a centrifugal ultrasonic stirrer. The stirring time is greater than or equal to 1 hour. The mixing may also include drying, and the drying may be performed after the stirring is completed. The drying may be performed by oven drying. The ultrasonic time of the centrifugal ultrasonic stirrer is 40 to 60 minutes, and the drying temperature is 120 to 140°C. The mixing may include sieving, and the sieving may be sieving through a 50 to 200# sieve.
[0019] In step S2, the crushing is performed at room temperature, and the crushing is performed by a vibrator, in which steel balls are placed, and the steel balls can be used to assist in crushing, and the material of the steel balls is 45 steel, which has been quenched and tempered. The screening can be performed by a 600# screen.
[0020] In step S3, the mixing is performed by a three-dimensional mixer, the mixing time is 25 to 60 minutes, and the mixing also includes sieving, and the sieving is sieving through a 100 to 200# sieve.
[0021] In step S4, the molding can be performed in a graphite mold, and the curing can be performed using a hot press with a pressure of 50 MPa. The curing includes post-molding treatment after heat and pressure maintenance at 900°C for 10 minutes.
[0022] The present invention provides a lithium tantalate wafer grinding wheel with high thermal conductivity and a preparation method thereof, which specifically include the following advantages:
[0023] (1) The annular abrasive layer is arranged on the end face of the substrate, which can reduce the grinding vibration during continuous grinding and reduce the grinding damage during the grinding process of the grinding wheel, thereby indirectly improving the surface quality of the machined part and reducing the scratches on the surface of the machined part;
[0024] Formula design of this product: The introduction of aluminum into the formula of the sample can increase the activity of silicon, thereby effectively removing the non-wettable silicon dioxide film on the surface of SiC powder particles, reducing the melt fluidity, and thus improving its wettability. The introduction of aluminum and magnesium elements generates the intermetallic compound AlCuMg phase during the hot pressing process, which effectively prevents the diffusion of copper and inhibits the interface reaction, thereby improving the strength and thermal properties of the SiC powder / Cu composite material.
[0025] (2) This product is manufactured by an integrated molding and curing method, that is, the cold pressing molding and high-temperature curing are carried out in the same set of molds, avoiding the need to take out the blank after cold pressing. This method avoids possible contamination of the product during the manufacturing process and stabilizes the quality of the product.
[0026] (3) The abrasive used in the present invention is cubic SiC powder, which acts as an abrasive during grinding and also as a factor for sharpening the blade, thus promoting grinding. This design allows the grinding wheel to continuously sharpen itself during grinding, thus ensuring the sharpness of the grinding wheel and avoiding the situation in which the traditional grinding wheel is not sharp enough and may burn the processing object during grinding.
[0027] (4) The overall strength of the grinding wheel designed with Si / Cu composite material in the present invention meets the requirements of the grinding wheel, and the performance of the product can effectively avoid burns on the workpiece surface.
[0028] (5) When processing lithium tantalate wafers, traditional grinding wheels have a high wear ratio and fast changes in grinding wheel profile. This change will cause uneven texture on the processed surface of the lithium tantalate wafer and may also cause low processing dimensional accuracy. When the volume fraction of SiC powder is 35%, the density of the sample is up to 98.81% (measured using the Archimedes principle), which increases the retention of the product and prevents the grinding wheel from decreasing rapidly due to processing and grinding during operation, thereby affecting the processing size of the workpiece. This design therefore improves the quality of the product.
[0029] In summary, the Brinell hardness of the grinding wheel prepared by the present invention can reach HRB 95, and the thermal conductivity of the grinding gold layer can reach 254.76W / (m·K). The product presents a relatively high thermal conductivity and a moderate hardness. This physical property is conducive to the processing of lithium tantalate wafer materials, and can cope with the surface discharge phenomenon of lithium tantalate wafers that may be caused by significant temperature changes, and the grinding scene that destroys lithium tantalate wafers, and effectively solves the problems of poor defective rate, easy burning of workpieces, low processing accuracy, and short life of grinding wheels during traditional grinding wheel processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Shown is a cross-sectional view of a grinding wheel according to the present invention.
[0031] Figure 2 Shown is a cross-sectional view of the conventional grinding wheel structure in Comparative Example 1.
[0032] Figure 3 Shown is a photograph of the grinding wheel obtained in Example 1.
[0033] Figure 4 and Figure 5 This is the SEM image of the grinding wheel prepared in Example 1.
[0034] Figure 6 SEM image of the artificial single crystal diamond in Example 1.
[0035] Figure 7 This is the SEM image of the SiC powder in Example 1.
[0036] Figure 8This is a photo of the lithium tantalate wafer being processed. DETAILED DESCRIPTION
[0037] See also Figures 1 to 8 .
[0038] like Figure 1 and Figure 2 As shown, the grinding wheel in the following embodiment includes an abrasive layer 1 and a substrate 2, a circular ring block is arranged along the circumference of the top of one end surface of the substrate 2, a through hole 3 is opened in the middle of the substrate 2, the circular ring block constitutes the abrasive layer 1, and the thickness D of the circular ring block is 6 mm.
[0039] The specific embodiments are as follows:
[0040] like Figure 1 As shown, the grinding wheel includes an abrasive layer 1 and a substrate 2. A circular ring block is arranged in an annular shape on the top end surface of the substrate 2. The circular ring block constitutes the abrasive layer 1. The specific embodiments are as follows:
[0041] Example 1
[0042] The grinding wheel of this embodiment includes the following powder raw materials in proportions by volume: 25 parts of artificial single crystal diamond powder, 35 parts of 26.52 μm green SiC powder (purity greater than or equal to 99.2%), 52 parts of 7.70 μm electrolytic copper powder (purity greater than or equal to 99.5%), 9 parts of 17.10 μm aluminum powder (purity greater than or equal to 99%), and 4 parts of 32.34 μm magnesium-aluminum alloy powder (purity greater than or equal to 98%), and the mass ratio of magnesium to aluminum in the magnesium-aluminum alloy powder is 9:1.
[0043] The preparation steps of the above-mentioned grinding wheel are as follows:
[0044] (1) Pour the green SiC powder, electrolytic copper powder, aluminum powder and magnesium aluminum alloy powder in the formula into alcohol and stir evenly, centrifuge and ultrasonicate for 60 minutes, and dry at 140° C. to obtain mixed material A;
[0045] (2) crushing artificial single crystal diamond (400#, model DI, USA) with a vibrator, ball milling, vibrating at 100 Hz for 10 minutes, and passing through a 600# sieve to obtain artificial single crystal diamond powder;
[0046] (3) Mixing material A and artificial single crystal diamond powder in a three-dimensional mixer at a rotation speed of 60 Hz for 25 minutes until mixed evenly to obtain a mixture B;
[0047] (4) Mixture B is placed in a cold-pressing and high-temperature curing integrated mold for production, and is kept at 50 MPa and 900° C. for 10 minutes, and finally the mold is removed to obtain the abrasive layer.
[0048] (5) The circular ring block is subjected to sandblasting, bonding (bonding to the substrate), rough turning of the substrate, fine turning of the substrate, and fine grinding of the circular ring block, and finally the finished grinding wheel is obtained after the quality inspection is qualified.
[0049] Example 2
[0050] The grinding wheel of this embodiment includes the following powder raw materials in proportions by volume: 18 parts of artificial single crystal diamond powder, 30 parts of green SiC powder (26.52 μm), 45 parts of 7.70 μm electrolytic copper powder (purity greater than or equal to 99.5%), 7 parts of 17.10 μm aluminum powder (purity greater than or equal to 99%), and 2 parts of 32.34 μm magnesium-aluminum alloy powder (purity greater than or equal to 98%), and the mass ratio of magnesium to aluminum in the magnesium-aluminum alloy powder is 9:1.
[0051] The preparation steps of the above-mentioned grinding wheel are as follows:
[0052] (1) Pour the green SiC powder, electrolytic copper powder, aluminum powder and magnesium aluminum alloy powder in the formula into alcohol and stir evenly, centrifuge and ultrasonicate for 60 minutes, and dry at 140° C. to obtain mixed material A;
[0053] (2) crushing the artificial single crystal diamond (400#) by a vibrator, ball milling, vibrating at 100 Hz for 10 minutes, and passing through a 600# sieve to obtain artificial single crystal diamond powder;
[0054] (3) Mixing material A and artificial single crystal diamond powder in a three-dimensional mixer at a rotation speed of 60 Hz for 25 minutes until mixed evenly to obtain a mixture B;
[0055] (4) Mixture B is placed in a cold-pressing and high-temperature curing integrated mold for production, and is kept at 50 MPa and 900° C. for 10 minutes, and finally the mold is removed to obtain the abrasive layer.
[0056] (5) The circular ring block is subjected to sandblasting, bonding (bonding to the substrate), rough turning of the substrate, fine turning of the substrate, and fine grinding of the circular ring block, and finally the finished grinding wheel is obtained after the quality inspection is qualified.
[0057] Comparative Example 1:
[0058] The grinding wheel structure with circumferentially distributed circular ring segment cutter heads has the same abrasive layer ratio as in Example 1, the same manufacturing process as in Example 1, and the same processing parameters are used to process lithium tantalate wafers.
[0059] Comparative Example 2:
[0060] The matrix structure of Comparative Example 2 is the same as that of Example 1, and the manufacturing process is the same as that of Example 1, wherein 35 parts of SiC powder are changed to 40 parts of SiC powder, and 52 parts of electrolytic copper powder are changed to 47 parts of electrolytic copper powder, and the remaining process methods and abrasive treatment methods are the same as those of Example 1.
[0061] Comparative Example 3:
[0062] The matrix structure of Comparative Example 3 is the same as that of Example 1, and the manufacturing process is the same as that of Example 1, wherein 35 parts of SiC powder are changed to 30 parts of SiC powder, and 52 parts of electrolytic copper powder are changed to 57 parts of electrolytic copper powder, and the remaining process methods and abrasive treatment methods are the same as those of Example 1.
[0063] Comparative Example 4:
[0064] The matrix structure of Comparative Example 4 is the same as that of Example 1, and the manufacturing process is the same as that of Example 1, wherein 9 parts of aluminum powder are replaced with 7 parts of aluminum powder, wherein 4 parts of magnesium-aluminum alloy powder are replaced with 6 parts of magnesium-aluminum alloy powder, and the remaining process methods and abrasive treatment methods are the same as those of Example 1.
[0065] Comparative Example 5:
[0066] The matrix structure of Comparative Example 5 is the same as that of Example 1, and the manufacturing process is the same as that of Example 1, wherein 9 parts of aluminum powder are replaced with 11 parts of aluminum powder, wherein 4 parts of magnesium-aluminum alloy powder are replaced with 2 parts of magnesium-aluminum alloy powder, and the remaining process methods and abrasive treatment methods are the same as those of Example 1.
[0067] Comparative Example 6:
[0068] The matrix structure of Comparative Example 6 is the same as that of Example 1, the formula design is the same as that of Example 1, wherein the diamond is not subjected to vibration crushing, and the rest of the process and abrasive treatment method are the same as those of Example 1.
[0069] The performance of the embodiments and comparative examples was evaluated under the conditions of a grinding wheel rotation speed of 1500 / rpm and a workpiece movement speed of 2 m / min. The evaluation results are shown in Table 1.
[0070] Table 1 shows the performance evaluation table of the grinding wheels prepared in the examples and comparative examples
[0071] Table 1
[0072]
[0073] The above results show that the abrasive layer of the circular ring block on the end face of the substrate is beneficial to improving the surface quality of the grinding wheel and reducing the occurrence of scratches and wear marks.
[0074] The above results show that the volume fraction of SiC powder is the main factor affecting the thermal conductivity of the composite material. When the product is designed and manufactured according to the volume fraction of SiC powder of 35%, the physical properties of the product meet the requirements of the present invention, which has a beneficial effect on increasing the life of the grinding wheel, improving the surface quality of the grinding wheel, and reducing the occurrence of scratches and damage to lithium tantalate wafers.
[0075] The above results show that the appropriate ratio of aluminum and magnesium elements is very important. The intermetallic compound AlCuMg phase is generated during the hot pressing process, which effectively prevents the diffusion of copper and inhibits the interface reaction, thereby improving the strength and thermal properties of the SiC powder / Cu composite material and directly improving the product service life.
[0076] The above results show that the diamond vibration crushing process is very important for improving surface quality and reducing damage rate during grinding. This is because large particles of diamond are crushed and the crystal becomes sharper.
[0077] The above embodiments are only illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. When the embodiments give a numerical range, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the technical personnel of the present art's grasp of the prior art and the records of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to implement the present invention. Anyone familiar with this technology can modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes completed by those with ordinary knowledge in the art without departing from the spirit and technical ideas disclosed in the present invention should still be covered by the claims of the present invention.
Claims
1. A lithium tantalate wafer grinding wheel, characterized in that: The lithium tantalate wafer grinding wheel comprises a base body and a circular ring block disposed circumferentially on the top end surface of the base body, wherein the circular ring block constitutes an abrasive layer of the grinding wheel, and the abrasive layer comprises the following powder raw materials in proportion by volume: 18-25 parts of artificial single crystal diamond powder; 30-35 parts of SiC powder; 45-52 parts of copper powder; 7-9 parts of aluminum powder; 2 to 4 parts of magnesium aluminum alloy powder.
2. The lithium tantalate wafer grinding wheel according to claim 1, characterized in that: The mass ratio of magnesium to aluminum in the magnesium-aluminum alloy powder is 9:
1.
3. The lithium tantalate wafer grinding wheel according to claim 1, characterized in that: Taking the total volume of SiC powder, copper powder, aluminum powder and magnesium-aluminum alloy powder as 100%, the volume fraction of the SiC powder is greater than 30% and less than 40%.
4. The lithium tantalate wafer grinding wheel according to claim 1, characterized in that: The SiC powder is green SiC powder, the copper powder is electrolytic copper powder, the aluminum powder is electrolytic aluminum powder, and the magnesium-aluminum alloy powder is electrolytic magnesium-aluminum alloy powder.
5. The lithium tantalate wafer grinding wheel according to claim 4, characterized in that: The average particle size of the SiC powder is 26-27 μm, the average particle size of the copper powder is 7-8 μm, the average particle size of the aluminum powder is 17-18 μm, and the average particle size of the magnesium-aluminum alloy powder is 32-33 μm.
6. The lithium tantalate wafer grinding wheel according to claim 1, characterized in that: The particle size of the artificial single crystal diamond powder is 20-24 μm.
7. A method for preparing a lithium tantalate wafer grinding wheel, characterized in that: The preparation method comprises the following steps: - S1: SiC powder, copper powder, aluminum powder and magnesium aluminum alloy powder are mixed to obtain a mixture A; - S2: crushing and sieving the artificial single crystal diamond to obtain artificial single crystal diamond powder; - S3: Mixture A and the artificial single crystal diamond powder are mixed to obtain mixture B; - S4: forming and curing the mixed material B to obtain the lithium tantalate wafer grinding wheel; The lithium tantalate wafer grinding wheel comprises a base body and a circular ring block arranged circumferentially on the top end surface of the base body, wherein the circular ring block constitutes an abrasive layer of the grinding wheel, and the abrasive layer comprises the following powder raw materials in proportion by volume: 18-25 parts of artificial single crystal diamond powder; 30-35 parts of SiC powder; 45-52 parts of copper powder; 7-9 parts of aluminum powder; 2 to 4 parts of magnesium aluminum alloy powder.
8. The preparation method according to claim 7, characterized in that: In step S1, the mixing includes screening, and the screening includes screening through a 50-200# sieve.
9. The preparation method according to claim 7, characterized in that: In step S2, the screening includes screening through a 600# sieve.
10. The preparation method according to claim 7, characterized in that: In step S3, the mixing includes screening, and the screening includes screening through a 100-200# sieve.
Citation Information
Patent Citations
Grinding wheel for grinding electronic packaging substrate material and preparation method thereof
CN111300288A
Grinding wheel for semiconductor packaging and grinding and preparation method thereof
CN116890306A
Magnesium-based composite material as well as preparation method and application thereof
CN117626076A
Supercapacitor composite sandwich laminate and uses thereof, as well as apparatus and method for its manufacture
DE102019120505A1
Rough Grinding Wheel Comprising A Core
US20190240809A1